A reorganizacao dos espacos mundiais apos a Segunda Grande Guerra (1945-1979). - Soares Pontes, B. M. (My University, 1981)
Examines the influence of class relations and political, ideological and structural shapes on international relations. Detente policy between the great world powers developed as a function of the basic interests of United States and Soviet Union. The analysis of underdeveloped countries' international policies is in accordance with processes of capitalistic accumulation and international labour division. -from English summary
The reorganisation of world spaces after the Second World War - 1945-1979